Meena, heroine of Afghanistan : the martyr who founded RAWA, the Revolutionary Association of the Women of Afghanistan - Chavis, Melody Ermachild (New York : St. Martin's Press, 2003)
Meena founded RAWA in 1977 as a 20 year-old Kabul University student. She was assassinated in 1987. This is the story of her struggle for democracy and women's rights in Afghanistan as well as a portrait of a courageous mother, poet and leader who symbolizes an entire movement of women.
Includes index.
Keywords: Meena, -- 1957-1987; Women social reformers -- Afghanistan -- Biography